TELA’AH AYAT HUKUM DAN HADIST TENTANG NUSYUZ - Lubis, Deka Ria Murni (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
Meanwhile, in verse 128 of the AN-Nisa letter, the punishment for husbands who commit Nusyuz on their wives is discussed. Husbands who commit Nusyuz can be seen from their attitude of ignoring their wives and neglecting their livelihood towards their wives and children. In verse 128 of Surah An-Nisa, it is explained that the punishment if the husband commits Nusyuz is that it is better to make peace with an agreement so that divorce does not occur, because peace is more important before Allah, even though there must be parties who feel aggrieved or find it difficult to accept the results of the peace.